Development of a vadose zone advanced monitoring system: Tools to assess groundwater vulnerability. Issue 6 (28th September 2022) - Linneman, Dorothy C.; Strickland, Christopher E.; Appriou, Delphine; Rockhold, Mark L.; Thomle, Jonathan N.; Szecsody, James E.; Martin, Paul F.; Vermeul, Vince R.; Mackley, Rob D.; Freedman, Vicky L.
Abstract: Performing repeat pore‐fluid sampling over long time‐scales can provide valuable information on unsaturated zone contaminants and their potential flux to ground water. This information can be used to manage groundwater remedies and identify contaminants that need to be sequestered in the vadose zone to minimize flux to ground water. Pore‐water samples are commonly used to obtain contaminant concentrations within the vadose zone, but existing methods are limited as they only provide a single sample at one location and time. The vadose zone advanced monitoring system (VZAMS) has been designed to integrate multiple technologies into a single down‐borehole system that allows for sampling of pore fluids (liquid and gas) to provide information about contamination and hydraulic conditions at multiple depths (∼0.3‐m intervals) within a cased borehole. Testing has been completed at the laboratory scale to verify the sampling elements of VZAMS, including geochemical testing for representative contaminants known to exist at the Hanford Site, located in southeastern Washington State. Physical tests focused on the ability of the sampler to draw fluid under unsaturated conditions. Initial geochemical testing showed that the stainless steel material used with the porous cuff may affect the sampled concentrations of redox‐sensitive contaminants under very dry conditions. Additional laboratory testing demonstrated that the VZAMS components are able to collect representative samples for substances of interest under expected field conditions. In this paper, the design and functionality of a novel instrument are demonstrated in support of subsequent testing in the field. Core Ideas: A new down‐borehole tool to sample vadose zone pore fluid was designed, constructed, and tested in the laboratory. Laboratory‐scale tests demonstrate the ability of the sampler components to effectively draw fluid samples. The downhole tool is able to collect representative fluid samples without geochemical alteration of constituents.